The Issue of Age Estimation in a Modern Skeletal Population: Are Even the More Modern Current Aging Methods Satisfactory for the Elderly?1, 2. Issue 1 (26th October 2016) - Cappella, Annalisa; Cummaudo, Marco; Arrigoni, Elena; Collini, Federica; Cattaneo, Cristina
Abstract: The main idea behind age assessment in adults is related to the analysis of the physiological degeneration of particular skeletal structures with age. The main issues with these procedures are due to the fact that they have not been tested on different modern populations and in different taphonomic contexts and that they tend to underestimate the age of older individuals. The purpose of this study was to test the applicability and the reliability of these methods on a contemporary population of skeletal remains of 145 elderly individuals of known sex and age. The results show that, due to taphonomic influences, some skeletal sites showed a lower survival. Therefore, the methods with the highest percentage of applicability were Lovejoy (89.6%) and Rougé‐Maillart (81.3%), followed by Suchey‐Brooks (59.3%), and those with the lowest percentage of applicability were Beauthier (26.2%) and Iscan (22.7%). In addition, this research has shown how for older adults the study of both acetabulum and auricular surface may be more reliable for aging. This is also in accordance with the fact that auricular surface and the acetabulum are the areas more frequently surviving taphonomic insult.